Effectiveness of petrissage massage manipulation in reducing delayed onset muscle soreness (DOMS) - Awaliyyah, Ulfatul Azizah; Raharjo, Hermawan Pamot; Saputro, Riki Edo; Irawan, Fajar Awang; Kresnajati, Sandhya (UIR Press, 2025)
Background: Delayed onset muscle soreness (DOMS) often occurs after intense physical activity and can limit subsequent performance. While common recovery methods such as ice therapy, stretching, and anti-inflammatory medications are widely used, they may not always be effective or free of side effects. Massage therapy—particularly the petrissage technique—offers a promising alternative by improving blood circulation, reducing muscle tension, and accelerating tissue recovery. Research Objectives: This study aims to evaluate the effectiveness of petrissage massage manipulation in reducing DOMS-related pain, offering a practical and non-invasive recovery method. Methods: A pre-experimental one-group pretest-posttest design was used. Participants experiencing DOMS were recruited from Klinik Satu Sehat. Pain levels were assessed using the Visual Analog Scale (VAS) before and after the intervention. Data were analyzed using the Shapiro-Wilk test for normality and a paired sample t-test to examine the effect of the massage treatment. Finding/Results: The study found a 38.7% reduction in pain levels after applying petrissage massage, indicating a significant improvement in muscle recovery. This reduction reflects the positive impact of increased blood flow and muscle relaxation facilitated by the massage technique. Conclusion: Petrissage massage manipulation is an effective technique for alleviating DOMS pain. It enhances blood flow, reduces muscle stiffness, and supports faster tissue healing. Future studies are encouraged to test this method across different populations, such as trained athletes and sedentary individuals, to explore potential variations in its effectiveness.